Clinicoserological features of antisynthetase syndrome (ASyS)-associated interstitial lung disease presenting to respiratory services: comparison with idiopathic pulmonary fibrosis and ASyS diagnosed in rheumatology services. Issue 1 (8th January 2021) - Barratt, Shaney L; Adamali, Havra H; Cotton, Caroline; Mulhearn, Ben; Iftikhar, Hina; Pauling, John David; Spencer, Lisa; Adamali, Huzaifa I; Gunawardena, Harsha
Abstract : Introduction: Antisynthetase syndrome (ASyS) is a rare autoimmune connective tissue disease (CTD), associated with autoantibodies targeting tRNA synthetase enzymes, that can present to respiratory (interstitial lung disease (ILD)) or rheumatology (myositis, inflammatory arthritis and systemic features) services. The therapeutic management of CTD-associated ILD and idiopathic pulmonary fibrosis (IPF) differs widely, thus accurate diagnosis is essential. Methods: We undertook a retrospective, multicentre observational cohort study designed to (1) evaluate differences between ASyS-associated ILD with IPF, (2) phenotypic differences in patients with ASyS-ILD presenting to respiratory versus rheumatology services, (3) differences in outcomes between ASySassociated with Jo-1 versus non-Jo-1 autoantibodies and (4) compare long-term outcomes between these groups. Results: We identified 76 patients with ASyS-ILD and 78 with IPF. Patients with ASyS were younger at presentation (57 vs 77 years, p<0.001) with a female predominance (57% vs 33%, p=0.006) compared with IPF. Cytoplasmic staining on indirect immunofluorescence was a differentiating factor between ASyS and IPF (71% vs 0%, p<0.0001). Patients with ASyS presenting initially to respiratory services (n=52) had a higher prevalence of ASyS non-Jo-1 antibodies and significantly fewer musculoskeletal symptoms/biochemical evidence of myositis, compared with those presenting to rheumatology services (p<0.05), although lung physiology was similar in both groups. There were no differences in high-resolution CT appearances or outcomes in those with Jo-1 versus non-Jo-1 ASyS-ILD. Conclusions: Extended autoimmune serology is needed to evaluate for ASyS autoantibodies in patients presenting with ILD, particularly in younger female patients. Musculoskeletal involvement is common in ASyS (typically Jo-1 autoantibodies) presenting to rheumatology but the burden of ILD is similar to those presenting to respiratory medicine.